Tumor odontogênico queratocístico: relato de caso - Faverani, Leonardo Perez [UNESP]; Ferreira, Gabriel Ramalho [UNESP]; Godoy, Paulo [UNESP]; Melo, Willian Moraes de [UNESP]; Fabris, Andre Luiz da Silva [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Garcia, Idelmo Junior Rangel [UNESP] (My University, 2013)
Introduction: The odontogenic keratocyst tumor (OKT) derived from dental lamina rests with particularities and specific histological features, with high rates of relapse and aggressive clinical behavior. Presents certain predilection for males, affecting the mandible of 60% to 80% of cases may be related to impacted tooth 25 to 45% of cases. Objective: To highlight the clinical, histopathological and imaging procedures of the OKT, as well as discuss the treatment of this injury. Case Report: To report a case of 10 years of age to look for the orthodontist to correct anterior open bite was observed in panoramic radiography radiolucent area in the region of the body of the mandible associated with pathological inclusion of the lower premolar. It was performed an incisional biopsy of the lesion and the histopathologic diagnosis was odontogenic keratocyst tumor. It was performed a CT scan to assess the extent of the injury and its relation to anatomic structures. How to conduct, we opted for the extraction of the deciduous molar and enucleation of the lesion, preserving the premolar included. The same goes on clinical and radiographic control 18 months, after removal of OKT obtaining the eruption of premolar that was involved in the injury. Final Comments: It is necessary to adopt protocols that include dental care knowledge of oral diagnosis, medical history and careful clinical evaluation without forgetting the need for histopathological confirmation.

Introdução: O Tumor Odontogênico Queratocístico (TOQ) deriva dos restos lâmina dentária com particularidades e aspectos histológicos específicos, com alto índice de recidiva e comportamento clínico agressivo. Apresenta certa predileção para o sexo masculino, acometendo a mandíbula de 60% a 80% dos casos, podendo estar relacionado a dente incluso de 25 a 45% dos casos. Objetivo: evidenciar as características clínicas, imaginológicas e histopatológicas do TOQ, bem como discutir sobre o tratamento desta lesão. Relato de Caso: Paciente de 10 anos de idade que ao procurar o ortodontista para correção de mordida aberta anterior, observou-se na ortopantomografia área radiolúcida, na região do corpo de mandíbula, associada à inclusão patológica do pré-molar inferior. Foi realizada biópsia incisional da lesão e o laudo histopatológico foi de tumor odontogênico queratocístico. Realizou-se uma tomografia computadorizada para avaliar a extensão da lesão e sua relação com as estruturas anatômicas. Como conduta, optou-se pela extração do molar inferior decíduo e enucleação da lesão, preservando o pré-molar incluso. O mesmo segue em controle clínico-radiográfico de 18 meses, após a remoção do TOQ obtendo-se a erupção do pré- molar que estava envolvido na lesão. Comentários Finais: É preciso adotar protocolos de atenção odontológica que incluem o conhecimento de diagnóstico bucal, anamnese e avaliação clínica criteriosa sem esquecer a necessidade de confirmação histopatológica.
Odontogenic keratocyst tumor: a case report
Keywords: World Health Organization; Neoplasms; Recurrence; Neoplasia; Organização Mundial da Saúde; Recidiva